2001
DOI: 10.1159/000048043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Weight on the Anticoagulant Response to Adjusted Therapeutic Dosage of Low-Molecular- Weight Heparin for the Treatment ofVenous Thromboembolism

Abstract: Data evaluating the safety of using weight-based dosing of low-molecular-weight heparin (LMWH) in obese patients are limited. Some manufacturers have recommended a maximum daily dose of LMWH not to be exceeded. The purpose of this study was to determine if body weight influenced the anticoagulant response to a weight-based dose of LMWH for the treatment of venous thromboembolism. Patients with serum creatinine levels <150 µmol/l receiving the LMWH , dalteparin 200 anti-Xa IU/kg based on actual body weight subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 19 publications
4
56
2
4
Order By: Relevance
“…9 Supporting the use of anti-factor Xa monitoring in patients with renal failure is the different potential for accumulation among the various LMWH preparations and the absence of a clear threshold of creatinine clearance for identification of patients at increased risk for accumulation. 41 Obese patients have been under-represented in treatment trials using LMWH, and although individual LMWH preparations have shown predictable antifactor Xa levels in this patient group, 42,43 measuring levels on at least 1 occasion seems prudent.…”
Section: Comparative Efficacy and Safety Of Ufh And Lmwhmentioning
confidence: 99%
“…9 Supporting the use of anti-factor Xa monitoring in patients with renal failure is the different potential for accumulation among the various LMWH preparations and the absence of a clear threshold of creatinine clearance for identification of patients at increased risk for accumulation. 41 Obese patients have been under-represented in treatment trials using LMWH, and although individual LMWH preparations have shown predictable antifactor Xa levels in this patient group, 42,43 measuring levels on at least 1 occasion seems prudent.…”
Section: Comparative Efficacy and Safety Of Ufh And Lmwhmentioning
confidence: 99%
“…Das gleiche fand sich für Tinzaparin bis 165 kg (24) und für Dalteparin bis zu 190 kg (25)(26)(27). Allerdings waren in diese Studien nur zufällig einige Patienten mit hohem BMI eingeschlossen.…”
Section: Aber Wer Möchte So Etwas Schon Jedesmal Ausrechnen? Ist Es üunclassified
“…Os trabalhos que avaliaram esse subgrupo usaram o peso atual dos pacientes para o cálculo da dose da HBPM a ser usada. (16)(17)(18)(19) Em pacientes com insuficiência renal grave, deve-se usar preferencialmente a HNF ao invés da HBPM. (C) A infusão contínua de HNF i.v.…”
Section: Hnf Ou Com Hbpm(a) Dando-se Preferência à Hbpm(a)unclassified